Facile Methods for the Synthesis of 8‐Ylidene‐1, 2, 3, 8‐tetrahydrobenzazecines. Issue 20 (15th May 2020) - Titov, Alexander A.; Kobzev, Maxim S.; Borisova, Tatiana N.; Listratova, Anna V.; Evenko, Tatiana V.; Varlamov, Alexey V.; Voskressensky, Leonid G.
Abstract : We have elaborated a general and simple microwave‐assisted method for the synthesis of original 8‐ylidene decorated benzazecines. We have shown that under the action of electron‐deficient alkynes in acetic acid the starting benzoannulated azacyclic allenes or 1‐alkyl(benzyl)‐1‐phenylethynyl‐substituted isoquinolines underwent transformations leading to benzazecines in high yields. In acetic acid all reactions proceeded smoothly to give target products, some of which were isolated as a mixture of E/Z‐isomers. Reactions with methyl propiolate in hexaflouroisopropanol (HFIP) featured regioselectivity and provided only E‐isomer of 8‐ylidene substituted benzazecines, whereas in case of acetylacetylene the sole products were azacyclic allenes. The key structure was unambiguously assigned by the means of X‐ray crystallography. Abstract : The main novelty of the present study is the development of the synthesis for an unusual and rare class of compounds – 8‐ylidenebenzazecines. The target compounds were synthesized via two strategies and obtained in high and good yields. The first method is an efficient MW‐assisted rearrangement of azacyclic allenes, the second one represents one‐pot protocol based on enlargement of tetrahydropyridine moiety to 8‐ylidene decorated azecine ring.